OPTIMISATION OF ERGONOMIC READING ROOM FACILITIES IN FORMING A CONDUCIVE CLIMATE IN PRAMA WIDYA PUSTAKA LIBRARY SMA NEGERI 1 WONOSARI - Savira, Ziana Maulida; Isnaini, Rohmatun Lukluk; Nurdin, Muh Nur Islam (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Reading room facilities in the library need attention, especially if the library does not provide ergonomic reading room facilities. Ergonomic facilities are equipment designed with attention to the comfort, safety and health of users in using the tool. This research aims to find out what kind of library reading room facilities apply ergonomic principles. This research is a qualitative research with a descriptive method. The data collection techniques used were observation, interview, and documentation. The results showed that Prama Widya Pustaka Library is very good and organized in the procurement, selection of tools, and maintenance of facilities and infrastructure. A conducive reading room climate has been implemented which is supported by ergonomic tables and chairs, good air temperature and humidity, and sufficient lighting. The completeness of ergonomic facilities and infrastructure has created a good reading space and built a conducive climate in the SMA Negeri 1 Wonosari Library so as to form the ENASE concept (effective, comfortable, safe, healthy and efficient). In line with that, it is hoped that this research will contribute to the school in providing good and comfortable facilities and infrastructure.